Structural Learning about Directed Acyclic Graphs from Multiple Databases - Qiang Zhao (Abstract and Applied Analysis)
We propose an approach for structural learning of directed acyclic graphs from multiple databases. We first learn a local structure from each database separately, and then we combine these local structures together to construct a global graph over all variables. In our approach, we do not require conditional independence, which is a basic assumption in most methods.